"Spiceophrenia": a systematic overview of "Spice"‐related psychopathological issues and a case report. (23rd July 2013) - Papanti, Duccio; Schifano, Fabrizio; Botteon, Giulia; Bertossi, Francesca; Mannix, Jason; Vidoni, Daniela; Impagnatiello, Matteo; Pascolo‐Fabrici, Elisabetta; Bonavigo, Tommaso
Abstract : Objectives: The use of synthetic cannabimimetics (SC; "spice" drugs) is increasing, especially among teenagers and young adults. In parallel with this, the number of studies describing intoxication episodes associated with psychotic symptoms in SC users is growing. We present both a systematic review of the related literature and a case report, which seems to highlight the existence of a possible association between SC use and psychosis. Methods: Some 223 relevant studies were here identified and reviewed. Out of these, 120 full text articles were assessed for eligibility, and 41 were finally included in the systematic review. Results: According to the available data from the studies here identified, SC's average age of users was 22.97 years, and the male/female ratio was 3.16:1. SC compounds most often reported in studies using biological specimen analysis were JWH‐018, JWH‐073, JWH‐122, CP‐47, 497, and JWH‐250. Mounting evidence seemed to suggest that psychotic symptoms such as hallucinations and delusions may occur in acute/chronic SC users. Conclusions: Although a clear causal link may not be here identified, the available evidence suggests that SC can trigger the onset of acute psychosis in vulnerable individuals and/or the exacerbation of psychotic episodes in those with a previous psychiatric history. Copyright © 2013 John Wiley & Sons, Ltd.